Enhancing Cultural Literacy: An Analysis of Primary School Students' Knowledge on Regional Culture Topics - Prihatiningsih, Prihatiningsih; Maryani, Enok; Supriatna, Nana; Sopandi, Wahyu; Sujana, Atep (Jurnal Ilmiah Sekolah Dasar, 2025)
Cultural literacy is an essential competence for students in the 21st century to navigate globalization while preserving regional cultural identity. The lack of students’ knowledge and concern for local culture can weaken national character values. This study aims to analyze the cultural literacy skills of primary school students in science, environment, technology, and society (IPAS) learning, focusing on conceptual understanding, knowledge of one’s own culture, and the implementation of cultural awareness. This research employed a quantitative descriptive method involving 30 fifth-grade primary school students as research subjects. Data were collected through tests and questionnaires, then analyzed using SPSS version 26 to determine the mean, maximum-minimum values, validity, reliability, and normality tests. The results showed that all instruments were valid and reliable, and the data were normally distributed. Based on the average results, 60% of students were categorized as moderate and 40% as low in their cultural literacy skills through the test, while the questionnaire results showed 66.7% moderate and 33.3% low. These findings suggest the importance of developing adaptive, culture-based learning models to enhance cultural literacy skills among primary school students.